Results of 100 Units of Botulinum Toxin Administration in Overactive Bladder Treatment - Karakeci, Ahmet; Keles, Ahmet; Ozan, Tunc; Orhan, İrfan; Onur, Rahmi (My University, 2021)
Objective: This study aimed to analyze the efficiencyand safety of botulinum toxin in patients who presented to urology clinicwith overactive bladder (OAB). Material and Methods: Between2015 and 2019, forty patients who were administered intravesical 100units of botulinum toxin for OAB treatment were evaluated retrospectivelyin terms of efficacy and safety. Efficacy was evaluated by usingthe treatment benefit scale (TBS) at 3 months after injection The qualityof life for OAB symptoms was evaluated via the incontinence qualityof life scale before treatment and at the 3rd month after treatment.Likewise, parameters such as incontinence, nocturia, urinary frequency,post-void residual urine values, maximum urine flow rate, number ofpads used were evaluated before and at the 3rd month after the procedure.Results: Significant increases were detected in post-procedureincontinence quality of life scores compared to pre-procedure, and inparallel with these results, significant increases were recorded in thepost-treatment questionnaire (38.5±15.0 and 69.9±6.3, respectively);p<0.001). In addition, according to the TBS results at the 3rd month,80% of the patients who underwent the procedure did benefit from thetreatment. Conclusion: Botulinum toxin injection still remains to bean effective option in refractory OAB treatment.
Keywords: Üroloji ve Nefroloji